Non-Canonical Roles of Apoptotic Caspases in the Nervous System - Dehkordi, Mahshid H.; Munn, Robert G. K.; Fearnhead, Howard O. (Frontiers in Cell and Developmental Biology, 2022)
Caspases are a family of cysteine proteases that predominantly cleave their substrates after aspartic acid residues. Much of what we know of caspases emerged from investigation a highly conserved form of programmed cell death called apoptosis. This form of cell death is regulated by several caspases, including caspase-2, caspase-3, caspase-7, caspase-8 and caspase-9. However, these “killer” apoptotic caspases have emerged as versatile enzymes that play key roles in a wide range of non-apoptotic processes. Much of what we understand about these non-apoptotic roles is built on work investigating how “killer” caspases control a range of neuronal cell behaviors. This review will attempt to provide an up to date synopsis of these roles.